The Effect of Individual Characteristics and Entrepreneurship on Rice Farming Performance - Imelda Imelda; Rakhmad Hidayat; Marisi Aritonang (Universitas Muhammadiyah Yogyakarta, 2022)
Entrepreneurship in the agricultural sector produces creative, innovative, and independent farmers who can improve farm performance. Therefore, this research aimed to determine the impact of individual characteristics and entrepreneurship on rice farming performance. The method employed in this research was a descriptive method to provide a qualitative description of individual characteristics and entrepreneurship in the performance of rice farming. The research was executed in one of the rice-producing centers in Kubu Raya Regency, West Kalimantan. The simple random sampling method was used in selecting farmers with 150 respondents selected as the sample size. Furthermore, the research variables involved were individual characteristics, farmer’s entrepreneurship, and rice farming performance. Data were collected using questionnaires, interviews, and observations, and analysis was performed using Structural Equation Modeling (SEM) with SMART-PLS software. The results showed that individual characteristics and entrepreneurship had a significant and positive effect on rice farming performance. Consequently, it can be concluded to improve rice farming performance, farmers suggested strengthening their characteristics, particularly those related to farming motivation, and enhancing their entrepreneurial characteristics through their task and outcome-oriented behavior.